Peningkatan Kompetensi Akademik Dosen Melalui Pelatihan Systematic Literature Review (SLR) - Dadang Sudrajat; Denni Pratama; Luthfi Adianto; Luthfiyyah Iffah Adella (CV. Multi Kreasi Media, 2023)
The quality of academic research is significantly influenced by the ability of lecturers to conduct systematic and comprehensive literature reviews. This Community Partnership Program aims to enhance the competence of Kopertip Indonesia lecturers in conducting Systematic Literature Reviews (SLR) as an essential part of the academic research process. This training is designed to provide an in-depth understanding of SLR methodology, including formulating appropriate research questions, effective literature search strategies, study inclusion and exclusion criteria, synthesis and analysis of literature data, and the preparation of high-quality SLR reports. It is expected that, through this training, Kopertip Indonesia lecturers can improve their ability to produce more relevant, comprehensive research that significantly contributes to the advancement of knowledge.